Preliminary Study on the Antibacterial Activities and Antibacterial Guided Fractionation of Some Common Medicinal Plants Practices in Itum Bahal, Kathmandu Valley of Nepal - Ravin Bhandari; Dhakaraj Pant; Kamal Singh Kathayat; Ramesh Bhattarai; Himal Barakoti; Jitendra Pandey; Nirmala Jamarkatel-Pandit (The Scientific World Journal, 2023)
The aim of this study was to evaluate the antibacterial activities of selected medicinal plant practices by a traditional healer of the Newar community in Itum Bahal, Kathmandu, Nepal. The antibacterial activities of the methanolic extract (1 mg/disc) of fifteen medicinal plants were screened against two Gram-positive bacteria (Staphylococcus aureus ATCC 25923 and Bacillus subtilis ATCC 6633) and two Gram-negative bacteria (Escherichia coli ATCC 25922 and Salmonella typhi CCM 5445) using the disc diffusion method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were calculated for the different fractions (hexane, chloroform, ethyl acetate, acetonitrile, and acetone) of the plants having a significant antimicrobial effect. Only Quercus infectoria G. Olivier (galls) and Mallotus repandus (Willd.) Müll.Arg. (seeds) exhibited prominent antibacterial effects. The acetone fraction from Q. infectoria had the strongest antibacterial effect, with a 41.00 mm inhibition zone against S. aureus. In contrast, the ethyl acetate fraction in M. repandus exhibited the highest efficacy, producing a 29.00 mm inhibition zone against S. typhi. In a similar manner, in the case of Q. infectoria, the acetoe fraction depicted the lowest MIC (0.19 mg/mL) and MBC (0.98 mg/mL) values against S. aureus, whereas the ethyl acetate fraction of M. repandus was most significant, showing the lowest MIC and MBC of 0.25 and 0.53 mg/mL, respectively, against S. typhi. This study suggested that the acetone extract of Q. infectoria galls can be used as a potential source against Gram-positive bacteria, whereas the ethyl acetate extract of M. repandus seeds could serve as a useful source to inhibit Gram-negative bacteria. Furthermore, extensive scientific investigation is mandatory to ensure the proper use of folk medicines.